2019
DOI: 10.1016/j.devcel.2019.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a Bilaterally Symmetric Pattern from Chiral Components in the Planarian Epidermis

Abstract: Highlights d Centrioles form a bilaterally symmetric pattern across the planarian epidermis d Within cells, centrioles are organized into a chiral asymmetric network d ODF2 and VFL1/3 help in establishing asymmetric connections between centrioles d Bilaterally symmetric patterns can emerge from chiral cellular structures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Recent studies on CCDC61 in the unicellular ciliate Paramecium tetraurelia showed that the protein plays a crucial role in the orientation of basal bodies and localizes at the interface between basal bodies and ciliary rootlets (Bengueddach et al, 2017). Consistent with these observations, CCDC61 was also shown to be important for the basal body orientation, and the generation of basal feet and ciliary rootlets in the multiciliated ventral epidermis of the flatworm Schmidtea mediterranea (Azimzadeh et al, 2012;Basquin et al, 2019), where its absence results in movement defects. Finally, in Xenopus laevis, the gene expression of CCDC61 was found to be upregulated by the expression of Multicilin, which promotes centriole biogenesis in multiciliated cells (Stubbs et al, 2012).…”
Section: Introductionmentioning
confidence: 68%
“…Recent studies on CCDC61 in the unicellular ciliate Paramecium tetraurelia showed that the protein plays a crucial role in the orientation of basal bodies and localizes at the interface between basal bodies and ciliary rootlets (Bengueddach et al, 2017). Consistent with these observations, CCDC61 was also shown to be important for the basal body orientation, and the generation of basal feet and ciliary rootlets in the multiciliated ventral epidermis of the flatworm Schmidtea mediterranea (Azimzadeh et al, 2012;Basquin et al, 2019), where its absence results in movement defects. Finally, in Xenopus laevis, the gene expression of CCDC61 was found to be upregulated by the expression of Multicilin, which promotes centriole biogenesis in multiciliated cells (Stubbs et al, 2012).…”
Section: Introductionmentioning
confidence: 68%
“…The distribution of Lrrcc1 and Ccdc61 at BBs is consistent with their observed requirement for correct MCC organization. This function is shared with Vfl1 (Lrrcc1) and Vfl3 (Ccdc61) orthologs, which are required to organize flagella/cilia in Chlamydomonas, Paramecium and planarians (Adams et al, 1985;Basquin et al, 2019;Bengueddach et al, 2017;Hoops et al, 1984;Wright et al, 1983). In contrast to studies in these species, however, we did not detect major rootlet structural defects upon Lrrcc1 and Ccdc61 depletion, suggesting the existence of redundant mechanisms to build up Xenopus BB appendages.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, polarization of BBs relies on their chiral construction, which mobilizes Lrrcc1 and Ccd61. This polarization allows the establishment of bilateral symmetry of the ventral multiciliated epidermis, which in turns governs the orientation of the worm movement (Basquin et al, 2019). In addition, retro-control loops exist between the different scales.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations